EDUKASI KEPERAWATAN PENERAPAN POLA HIDUP SEHAT DALAM MENCEGAH KEJADIAN STROKE BERULANG DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Lubis, Shofi Manja Sari; Susanti, Deni; Gea, Handerman Vitu (SINERGI : Jurnal Riset Ilmiah, 2025)
Stroke is a condition that occurs when the blood supply to a part ofthe brain is suddenly disrupted, causing the death of some brain cells due to impaired blood flow resulting from a blockage or rupture of a blood vessel in the brain. Stroke is one ofthe leading causes of death and disability. Efforts to prevent recurrent strokes can be made through the modification of a healthy lifestyle, such as proper dietary management, regular physical activity, and health education. This study aims to evaluate the effectiveness of nursing education in the application of a healthy lifestyle among post-stroke patients at Tk II Putri Hijau Hospital Medan. The method used is descriptive, employing a case study design involving two patients using a medical-surgical nursing care approach, which includes assessment, diagnosis, planning, implementation, and evaluation. The inclusion criteria involved male and female stroke patients who were willing to participate as respondents. The results showed that the education provided by nurses on healthy lifestyles had a positive impact on patients' behavioral changes and increased the knowledge of both patients and their families regarding the adoption of a healthy lifestyle. This study emphasizes the crucial role of nurses in delivering health education on healthy lifestyle practices to prevent recurrent strokes by providing appropriate and continuous education aimed at reducing the risk of recurrent stroke through enhanced knowledge and behavior modification in patients